The Influence of Various Tensile and Shear Reinforcement Configurations on the Ultimate Capacity and Failure Mechanisms of Reinforced Concrete Beams - Ahmed S. Elamary; Ibrahim A. Sharaky; Fahad M. Alharthi; Ayman El-Zohairy; Mostafa M. A. Mostafa (Buildings)
This study comprehensively examines the impact of various tensile and shear reinforcement arrangements on the ultimate capacity and failure mode of reinforced concrete (RC) beams. This study encompasses theoretical, experimental, and numerical approaches. The experiment consisted of six beams (three 2.0 m long beams and three beams measuring 1 m in length) and had unique shear and tensile reinforcement setups. Truss bars and stirrups were used as shear reinforcement, while steel plates and bars were used as tensile reinforcement. The objective was to assess and compare the impact of the arrangement of tensile and shear reinforcement on the bending and shear strength of beams. The findings suggest that concrete beams reinforced with steel plates and stirrups had the highest load-carrying capacity when compared with conventional beams. Furthermore, a beam using truss bars with only 51.1% of the shear reinforcement area provided by stirrups achieved approximately 87% of the load capacity of its stirrup-reinforced counterpart. Additionally, increasing the yield strength of the steel plates from 420 MPa to 520 MPa enhanced beam stiffness and resulted in a 6% increase in ultimate load capacity.